2013
DOI: 10.1016/j.seizure.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Aroma helps to preserve information processing resources of the brain in healthy subjects but not in temporal lobe epilepsy

Abstract: The current results show that exposure to the ylang-ylang aroma reduced information processing resources in healthy subjects but had limited effects in patients with TLE. We suggest that impaired higher-order olfactory processing in TLE patients may inhibit the effects of the ylang-ylang aroma on the P300.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Furthermore, reduction of the amplitude of auditory P300 which is associated with the higher cognitive processing was observed in healthy volunteers during inhalation of ylang-ylang aroma, suggesting a relaxing effect of aroma on cognitive function. Watanabe and colleagues [ 100 ] elucidated the effect of ylang-ylang aroma on the auditory P300 of healthy individual and patient with temporal lobe epilepsy (TLE) who have impaired odor identification. The study demonstrated exposure to ylang-ylang aroma prolonged latencies of P300 in both control and TLE groups while only significant reduction of P300 amplitudes in healthy volunteers was observed.…”
Section: Effects On Mood and Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduction of the amplitude of auditory P300 which is associated with the higher cognitive processing was observed in healthy volunteers during inhalation of ylang-ylang aroma, suggesting a relaxing effect of aroma on cognitive function. Watanabe and colleagues [ 100 ] elucidated the effect of ylang-ylang aroma on the auditory P300 of healthy individual and patient with temporal lobe epilepsy (TLE) who have impaired odor identification. The study demonstrated exposure to ylang-ylang aroma prolonged latencies of P300 in both control and TLE groups while only significant reduction of P300 amplitudes in healthy volunteers was observed.…”
Section: Effects On Mood and Cognitive Performancementioning
confidence: 99%
“…The study demonstrated exposure to ylang-ylang aroma prolonged latencies of P300 in both control and TLE groups while only significant reduction of P300 amplitudes in healthy volunteers was observed. The absence of P300 amplitudes reduction in TLE patients suggested that their information processing was not altered during the exposure to ylang-ylang aroma or the fact that TLE patients had lower P300 amplitudes under odourless condition as compared to the controls [ 100 ].…”
Section: Effects On Mood and Cognitive Performancementioning
confidence: 99%
“…A particular amount of fragrance oil was administered using an oxygen pump system through a plastic tube via respiratory masks (flow rate at 2 L/min) [12]. In another report, a known volume of diluted fragrance oil was added in a plastic bag and administered through a mask [63]. In a recent study, a nebulizer was used for the administration of fragrance oil.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%
“…These changes were associated with the increase of positive emotions such as the feeling of well-being, or feeling active, fresh and romantic. Watanabe et al [63] found that impaired higher-order olfactory processing in temporal lobe epilepsy patients may inhibit the effects of the ylang-ylang aroma on the P300. Yoto et al [103] investigated the memory task performance and the central nervous activity after smelling two kinds (Koushun and Kouju) of pan-fired Japanese green tea to examine their physical and psychological effects.…”
Section: Effect Of Inhalation Of Fragrance On Eeg Activitymentioning
confidence: 99%
“…When compared with the control group, a decrease of P300 amplitude and an increase of P300 latency were observed in patients with MTS. Watanabe et al [ 60 ] found that P300 latencies were prolonged by the ylang-ylang fragrance in both patients with TLE and healthy subjects. The P300 amplitude was significantly reduced by the ylang-ylang fragrance in healthy subjects.…”
Section: P300 and Epilepsymentioning
confidence: 99%